Analysis of Lesunirad in Rat Plasma with an Improved Sensitivity by CZE-MS/MS Detection: Application to Pharma- cokinetic Study. Issue 6 (2nd November 2021) - Deepakumari, H.N.; Shyla, B; Sowmya, P.T.; Revanasiddappa, H.D.
Abstract: Lesunirad is an uricosuric drug that inhibits the uric acid transporter-1 (URAT-1) and organic anion transporter-4 within the proximal renal tubule, which are involved in acid reabsorption within the kidney 1. In this article, a new CZE coupled with electron-spray ionization - tandem MS approach has been employed for lesunirad in rat plasma after precipitation of plasma proteins by acetonitrile using internal standard, loratadine. By one step-deproteinization approach, plasma sample was set using 0.3 mL of acetonitrile mixed with 0.3 mL plasma specimen. Electrophoretic segregation and detection of lesunirad from plasma samples were achieved by using fused silica capillary made up of sheath liquid (SL) composition of water consisting of 0.25 % of formic acid and methanol in the ratio of 40:60 and BGE containing 25 mM of ammonium formate buffer solution, injected at a rate of flow of 0.3 nL/min. Thereafter, analytes were monitored using ESI with positive ion MRM and was applied for the evaluation of the precursor to product ion at m/z 406 → 221 for lesinurad and m/z 383 → 337 for IS loratadine. The method showed better linearity in the range of 10-1000 ng/mL and was authenticated as stated by the current ICH regulations and the results obtained were within the acceptable limits. Due to high sensitivity, less time consuming and sample volume requirement, finally, the CZE-MS was effectively applicable to pharmacokinetic studies of lesunirad in rats and the concentration-time profile of CZE-MS in rat plasma sample was found to correlate well when compared to UHPLC-MS/MS assay available in the literature. GRAPHICAL ABSTRACT: UF0001